Integrated Ground‐penetrating Radar and Archaeological Surveys in the Ancient City of Hierapolis of Phrygia (Turkey). Issue 4 (17th September 2013) - Leucci, G.; Di Giacomo, G.; Ditaranto, I.; Miccoli, I.; Scardozzi, G.
ABSTRACT Hierapolis of Phrygia (Turkey) was one of the most important Hellenistic, Roman and Byzantine city in Asia Minor. The Italian Archaeological Mission in more than 50 years of activity has brought to light and restored many monuments of the ancient city, helping to understand the urban layout in the various periods of its history. In 2011 ground‐penetrating radar (GPR) prospection, with the aim of supporting the archaeological excavations and surveys, was performed in some important sample areas by a team of the Institute for Archaeological and Monumental Heritage of the National Research Council of Italy. The analysis of the GPR measurements revealed many anomalies that could be ascribed to archaeological structures, as well as other anomalies of presumable natural origin. The data collected were georeferenced in the digital archaeological map of Hierapolis using a RTK‐GPS system. Copyright © 2013 John Wiley & Sons, Ltd.